Who’s the winner: the dromological phenomenon in Shopee live streaming - Yumianti, Iin; Putri Ramadaniar; Kusumajanti (Jurnal Studi Komunikasi, 2025)
Changes in shopping behaviour is occurring as a result of the advances in e-commerce technology, with consumers shifting from traditional shopping methods to digital shopping. One of the most widely used e-commerce platforms in Indonesia is Shopee. Through its live streaming feature, Shopee plays a significant role in driving the digital economy and creating a ‘dromological’ phenomenon in the postmodern age. This study aimed to explore how the dromological process, as proposed by Paul Virilio, can be applied in Shopee live streaming and its probable impact on consumer behaviour. This research adopts a qualitative approach, specifically a netnographic case study, focusing on the flash sale Shopee Live promo program 11.11 which was held last November 11, 2024, hosted by Shani Amelia, Lila Azmina, and Alabisyir. The data collection involved gathering digital data from the Shopee application as this research’s primary data and is supported by the secondary data which was conducted through interviewing participants that were selected using purposive sampling technique. The findings reveal that the dromological process manifests in the rapid distribution of promotional information, the emergence of price wars in the digital marketplace, and the creation of modern endo-colonization, where the accelerated pace of information highly influences consumer behaviour. This study offers valuable insights into the intersection of speed, information, and consumer decisions within the growing e-commerce landscape.